2015
DOI: 10.1103/physreve.92.013012
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of raindrop formation due to the tangling-clustering instability in a turbulent stratified atmosphere

Abstract: Condensation of water vapor on active cloud condensation nuclei produces micron-size water droplets. To form rain, they must grow rapidly into at least 50-100 µm droplets. Observations show that this process takes only 15-20 minutes. The unexplained physical mechanism of such fast growth, is crucial for understanding and modeling of rain, and known as "condensation-coalescence bottleneck in rain formation". We show that the recently discovered phenomenon of the tangling clustering instability of small droplets… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…The projection of each particle motion on z axis can be described by the following equations [ Elperin et al , ; Belan et al , ]: leftitalicdVitalicdt=VvTτSt1+g,italicdvitalicdt=vvTτSt2+g, where τ St1,2 are the Stokes times for large and small particles, v T is a turbulent velocity, and g is the acceleration of gravity. We can use expressions in complex amplitudes because the equations are linear and the turbulent velocity can be represented as a Fourier integral.…”
Section: Methodsmentioning
confidence: 84%
See 1 more Smart Citation
“…The projection of each particle motion on z axis can be described by the following equations [ Elperin et al , ; Belan et al , ]: leftitalicdVitalicdt=VvTτSt1+g,italicdvitalicdt=vvTτSt2+g, where τ St1,2 are the Stokes times for large and small particles, v T is a turbulent velocity, and g is the acceleration of gravity. We can use expressions in complex amplitudes because the equations are linear and the turbulent velocity can be represented as a Fourier integral.…”
Section: Methodsmentioning
confidence: 84%
“…The projection of each particle motion on z axis can be described by the following equations [Elperin et al, 2015;Belan et al, 2016]:…”
Section: Motion Equations and Turbulence Representationmentioning
confidence: 99%
“…Saffman and Turner () showed that the rapid growth of “small” cloud droplets (of sub‐Kolmogorov size and whose Stokes number ( St ) ≪ 1; the latter is the ratio of droplet response time to Kolmogorov time‐scale (Davidson, ) demands turbulence with a dissipation rate ∼2, 000 cm 2 ·s −3 which rather lies at the higher end of the dissipation rates for cumulus clouds. However, Maxey () showed that inertial particles in a turbulent flow leave high‐vorticity regions to accumulate in high‐strain regions, which phenomenon is now called clustering (or preferential concentration or accumulation effect); since then more mechanisms for inertial particle clustering have been proposed (Mehlig and Wilkinson, ; Coleman and Vassilicos, ; Bec et al ., ; Bragg et al ., ; Elperin et al ., ), see Gustavsson and Mehlig () or Pumir and Wilkinson () for a review. Droplet clustering further enhances the collision rate because the number density in the vicinity of a droplet is now statistically higher; the enhancement is measured either by comparison with Saffman and Turner ()'s formula (because droplets do not cluster when St → 0 or St → ∞ ) or by computing the radial distribution function at contact between droplets (Sundaram and Collins, ).…”
Section: Introductionmentioning
confidence: 99%
“…(42)- (47) in [26] and Eqs. (17) and (18) in [27]. The correlation function (R) takes into account particle clustering.…”
Section: Particle Correlation Functionmentioning
confidence: 99%
“…Recent analytical studies [26,27] and laboratory experiments [28] have shown that the particle clustering can be much more effective in the presence of a mean temperature gradient. In this case, the turbulence is temperature stratified and the turbulent heat flux is not zero.…”
Section: Introductionmentioning
confidence: 99%